Republic of Moldova : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
In this paper, the following statistical data were listed in detail: GDP by both expenditure and sector, industrial production by sector, agricultural and industrial production indices, structure of agricultural land ownership, agricultural production by sector, nominal wages by sector, monthly prices, exchange rates, employment by sector, exchange rates, central and local government operations, central and local government expenditure, monetary survey, balance of payments, composition and direction of trade, accounts of the national bank of Moldova, import tariff developments, and external debt indicators.